Understanding Human Behavior Development with Spirituality: Critical Insights into Moral Flourishing - Miftachul Huda; Sultan Salem (Ulumuna, 2022)
This paper examines the flourishing of moral enhancement through a critical investigation of Al-Zarnūjī’s Ta‘lim al-Muta‘allim. The critical reviews of the literature from refereed and peer-reviewed articles were employed using thematic topic analysis on the flourishing of moral enhancement with a special reference to Al-Zarnūjī's Ta‘lim al-Mutallim, in giving an insightful value to spiritual engagement. The results show that the subsequent phase of moral flourishing with spirituality comes from niyyah (goal-oriented commitment) as the enhanced enthusiasm derived from the continued consistency of doing goodness in the human morality indicator. This is followed with faqīhan mutawarri‘an (clear comprehension with carefulness) as comprehending personal behaviour with knowledge and moral quality. The following point supported muwāḍabah (thorough attempts) as the expansion of wide-ranging performance made for moral development and continued into sustaining individual behavioural growth with a spiritual quality. Furthermore, a discussion of implications serves to contribute to human behavioural development, with spirituality detailed into moral behaviour through spiritual quality enhancement, as well as the continued awareness of ethical behaviour sustainability and knowledgeable practice quality progression.